2005
DOI: 10.1136/emj.2004.015255
|View full text |Cite
|
Sign up to set email alerts
|

Have the implementation of a new specialised emergency medical service influenced the pattern of general practitioners involvement in pre-hospital medical emergencies? A study of geographic variations in alerting, dispatch, and response

Abstract: Objectives: Emergency medical service systems in Norway are based on equity and equality. A toll free number (113) and criteria based dispatch are crucial components. The establishment of an emergency medical system (EMS) manned by an air and ground emergency physician (EP) has challenged the role of the general practitioner (GP) in emergency medical care. We investigated whether there were any geographical differences in the use of 113, alerts to GPs by the emergency medical dispatch centres (EMDCs), and of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 10 publications
3
15
0
Order By: Relevance
“…This may explain some of the differences found between RGPs working in central and remote areas. Similar to a previous Norwegian study,10 we also found that RGPs are more often on “call-outs” in remote municipalities.…”
Section: Discussionsupporting
confidence: 90%
“…This may explain some of the differences found between RGPs working in central and remote areas. Similar to a previous Norwegian study,10 we also found that RGPs are more often on “call-outs” in remote municipalities.…”
Section: Discussionsupporting
confidence: 90%
“…The association (odds ratio) between rural areas and call-out is strong. The findings support the conclusion in an earlier study done in the area of EMCC Stavanger (90).…”
Section: Alarms To Doctors On-call In the Emergency Primary Care Servsupporting
confidence: 92%
“…Access should be by a widely publicized internationally recognized calling number such as 112 in Europe or 911 in North America (Britvic et al, 2007;ICAR, 2010;Vaardal et al, 2005). All persons dispatching a helicopter should be aware of the specific problems encountered in mountainous or wilderness areas.…”
Section: Dispatchingmentioning
confidence: 99%